Elizabeth McAnally, Loving Water Across Religions: Contributions to an Integral Water Ethic - Peppard, Christiana Z. (Journal for the study of religion, nature and culture, 2021)
Elizabeth McAnally, Loving Water Across Religions: Contributions to an Integral Water Ethic (Maryknoll: Orbis Books, 2019), 180 pp., $26.00 (pbk), ISBN: 978-1-62698-307-6.